Implementation for Soldier Communication Based on Session Initiation Protocol: A Systematic Literature Review - Sabila, Sandhya Hizrian (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
In tactical networks, group conversation programs are needed, which includes positioning and sharing of information (Situational Awareness information) and Push-to-Talk voice conversation. VoIP has a kind of protocol in order that conversation with the IP network (internet) can engage with every other (connect). There are numerous protocols that have emerged, however together with the improvement of conversation that requires performance and decrease costs, the VoIP protocol emerged, particularly SIP or Session Initiation Protocol. The capability of the SIP protocol can be very appropriate to be used as communication amongst army forces in forested battle areas. The purpose of this paper is to provide an entire and primarily based totally analysis, now no longer best of strategies however additionally of information sources, objectives, date ranges, sorts of information, information frequency, and size accuracy. The paper additionally identifies a few last troubles to be solved as destiny instructions for SIP-primarily based totally soldier communications programs research. There are sixteen recent research on soldier communication from 2016 to 2021 with the shape of a scientific literature review.